Quantum well engineering of InAlAs/InGaAs HEMTs for low impact ionization applications - Gomes, Umesh P.; Chen, Yiqiao; Kabi, Sanjib; Chow, Peter; Biswas, Dhrubes (Current applied physics, 2013)
The performance of InAlAs/InGaAs quantum well field effect transistors are subject to high impact ionization and band-to-band tunneling (BTBT) due to its narrow bandgap feature. In this work, the energy gap is engineered using strain and quantization techniques to increase the effective energy gap leading to low impact ionization and BTBT leakage current. It is shown that the impact ionization is reduced in 5 nm channel device as compared to 13 nm device with onset at approximately Egeff/q. Also the band-to-band-tunneling current is reduced due to the increase in effective energy gap. We have also investigated the effects of quantum well engineering on the dc performance of InGaAs HEMTs. ► We investigate the effects of strain and channel quantization on impact ionization and BTBT. ► The effective energy gap is increased due to strain and quantization. ► Increasing the energy gap reduces leakage current and increases the onset of impact ionization in the channel.